Case Report: Therapeutic Management of Anaplasma spp. Infection in A Dog from Fiji Island - Yogeswaranthan, Prashanth (Universitas Airlangga, 2025)
Anaplasmosis is an emerging tick-borne zoonotic pathogen in dogs and humans that has recently gained attention in parasitology and microbiology study groups worldwide. This infection has been reported in regions worldwide. There are no reported cases of exposure to Anaplasma spp. canine or human patients in the Fiji Islands. This is the first reported case of canine Anaplasma spp. infectious canine cyclic thrombocytopenia in the Fiji Islands. Canine patients were presented to Pacific Animal Shelter and Hospital (PASH) in the Fiji Islands were screened for Anaplasma spp. antibodies using a commercial kit based on an enzyme-linked immune assay. Anaplasma spp. infection was diagnosed based on major clinical data, hematological findings and positive serology tests. The case was diagnosed as canine Anaplasmosis and was successfully treated with Doxycycline and other supportive treatments.